Zakat Management Concept to Accelerate Health and Economic Recovery during the COVID-19 Pandemic - Chotib, Moch (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: The COVID-19 pandemic impacts the zakat management of zakat institutions. Zakat is an Islamic obligation to donate a portion of one’s wealth. This is because the income of the muzakki (the people who pay the zakat) decreased. The pandemic caused the decline of people’s income, thus increasing the number of mustahik (zakat recipients). This condition encourages the application of a zakat empowerment concept that aims to accelerate people’s economy. AIM: This paper aims analyze the zakat empowerment concept in the health and welfare aspects during the pandemic, to obtain legal protection based on the benefit (maslahah) and policy theories. METHODS: This qualitative research aims to focus on the zakat empowerment concept in the aspects of health and welfare during the pandemic. RESULTS: The zakat institutions may channel the zakat to the mustahik who are affected by the pandemic in the form of medicine, COVID-19 vaccines, and capitals to families whose breadwinners lost their jobs or died due to the pandemic. This qualitative research aims to analyze the zakat empowerment concept during the pandemic in the aspects of health and welfare and its legal protection based on benefit (maslahah) theory and the policy theory. According to the policy theory, the zakat empowerment concept in the health and economic sectors during the pandemic is according to Law No. 23 of 2011 on Zakat Management. CONCLUSION: According to the maslahah theory, it is categorized as a maslahah hajiyah from the basis of maslahah al-mursalah. However, to give legal certainty and legal protection, the zakat empowerment concept in the health and economic sectors during the pandemic should be validated in legal regulation.